2004
DOI: 10.1146/annurev.arplant.55.031903.141758
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanisms for Organic Forms of Carbon and Nitrogen Between Source and Sink

Abstract: Sugars and amino acids are generated in plants by assimilation from inorganic forms. Assimilated forms cross multiple membranes on their way from production sites to storage or use locations. Specific transport systems are responsible for vacuolar uptake and release, for efflux from the cells, and for uptake into the vasculature. Detailed phylogenetic analyses suggest that only proton-coupled cotransporters involved in phloem loading have been identified to date, whereas systems for vacuolar transport and effl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
301
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(313 citation statements)
references
References 182 publications
7
301
0
5
Order By: Relevance
“…In this study, most of SWEET proteins contain two MtN3_slv domains, though one or three domains are also founded in some genes, suggesting that the function is highly conservative in the evolutionary process. Most of the known sugar transporter proteins are located on the plasma membrane and are involved in the transport of sugars (Lalonde et al 2004). In this study, all members of the SWEET family identified from cotton were located on the plasma membrane, which is consistent with previous research of SWEETs localization (Chen et al 2012).…”
Section: Cotton Sweets Have Been Highly Conserved During the Evolutionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, most of SWEET proteins contain two MtN3_slv domains, though one or three domains are also founded in some genes, suggesting that the function is highly conservative in the evolutionary process. Most of the known sugar transporter proteins are located on the plasma membrane and are involved in the transport of sugars (Lalonde et al 2004). In this study, all members of the SWEET family identified from cotton were located on the plasma membrane, which is consistent with previous research of SWEETs localization (Chen et al 2012).…”
Section: Cotton Sweets Have Been Highly Conserved During the Evolutionsupporting
confidence: 91%
“…Sugar is a major carbon source and energy source for higher plants in their growth and development (Walmsley et al 1998;Lalonde et al 2004;Chen et al 2010;Chen et al 2012). Higher plants can use convert CO 2 into organic carbon in photosynthetic leaves (the source).…”
Section: Introductionmentioning
confidence: 99%
“…SUTs contain 12 transmembrane domains that form a pore permitting Suc transport through the membrane. Biochemical studies have shown Suc transport activity for numerous dicot as well as monocot SUTs (for recent reviews, see Aoki et al, 2003;Kü hn, 2003;Lalonde et al, 2004;Sauer, 2007). In multiple plants, it has been shown that SUT RNA and/or protein abundance is regulated by Suc (Chiou and Bush, 1998;Aoki et al, 1999;Matsukura et al, 2000;Vaughn et al, 2002;Ransom-Hodgkins et al, 2003), but the genes that control SUT expression have not been identified.…”
Section: Sutsmentioning
confidence: 99%
“…AtSUC2), but type II (OsSUT1 and AtSUC3, which is identical to AtSUT2) and type III (HvSUT2 and AtSUT4, which is identical to AtSUC4) contained both monocot and dicot proteins (Aoki et al, 2003;Lalonde et al, 2004). With increasing numbers of SUT sequences available, phylogenetic analysis divided the SUTs into four clades, splitting the type II subfamily into two groups (Sauer, 2007).…”
Section: Sutsmentioning
confidence: 99%
See 1 more Smart Citation